Natural ventilation strategies for indoor thermal comfort in Mediterranean apartments - Eftychia Spentzou; Malcolm Cook; Stephen Emmitt (2017)
Natural ventilation strategies as effective low energy refurbishment solutions are identified within this research study, for an existing urban multi-storey apartment building in Athens, representative of over four-million Greek urban residential buildings. Retrofit strategies were evaluated using occupant comfort criteria and the existing ventilation strategy, for a single apartment using dynamic thermal simulations. These strategies included individual day and night ventilation, a wind-catcher and a dynamic façade. Suitable openings operation in response to environmental parameters provided sufficient day and night ventilation and occupant comfort. The inclusion of a wind-catcher yielded very little improvement to the ventilation performance. However, the combined operation of the wind-catcher and the dynamic façade delivered operative temperature reductions of up to 7oC below the base-case strategy, and acceptable ventilation rates for up to 65% of the cooling period. The successful performance of the proposed strategies highlights the potential for reducing energy consumption and improving thermal comfort in a large number of buildings in hot climates.